Application of new pedagogical technologies in the course of the lesson (Eurasian Research Bulletin, 2024)
This article explores the integration of new pedagogical technologies into classroom settings to enhance teaching and learning experiences. It delves into the literature surrounding the efficacy of these technologies, analyzes various methods of implementation, presents findings from recent studies, engages in a discussion on the implications of these results, and concludes with suggestions for future directions in educational practices.